Design and use of Chikungunya virus replication templates utilizing mammalian and mosquito RNA polymerase I mediated transcription - Utt, A; Rausalu, K; Jakobson, M; Männik, A; Alphey, L; Fragkoudis, R; Merits, A (American Society for Microbiology, 2019)
Chikungunya virus (CHIKV) is a mosquito-borne alphavirus. It has a positive sense RNA genome that also serves as the mRNA for four non-structural proteins (nsPs) representing subunits of the viral replicase. Coupling of nsP and RNA synthesis complicates analysis of viral RNA replication. We developed trans-replication systems, where production of replication competent RNA and expression of viral replicase are uncoupled. Mammalian and mosquito RNA polymerase I promoters were used to produce non-capped RNA templates, which are poorly translated relative to CHIKV replicase generated capped RNAs. It was found that, in human cells, constructs driven by RNA polymerase I promoters of human and Chinese hamster origin performed equally well. In contrast, RNA polymerase I promoters from Aedes mosquitoes exhibited strong species specificity. In both mammalian and mosquito cells, novel trans-replicase assays had exceptional sensitivity, with up to 105-fold higher reporter expression in the presence of replicase relative to background. Using this highly sensitive assay to analyse CHIKV nsP1 functionality, several mutations that severely reduced, but did not completely block, CHIKV replicase activity were identified: (i) tagging the N-terminus of nsP1 with eGFP; (ii) mutations D63A and Y248A blocking the RNA capping; (iii) mutation R252E affecting nsP1 membrane anchoring. In contrast, a mutation in the nsP1 palmitoylation site completely inactivated CHIKV replicase in both human and mosquito cells and was lethal for the virus. Our data confirms that this novel system provides a valuable tool to study CHIKV replicase, RNA replication and virus-host interactions.